Kinetics of Steam Gasification of Brown Coal and Volatile-Char Interactions - Kajitani, Shiro; Tay, Hui-Ling; Zhang, Shu; Li, Chun-Zhu (ICMS Pty Ltd, 2010)
Victorian brown coal has high reactivity for gasification because of catalysis of inherent AAEM species. It was, however, found recently that the inhibitory effects of the volatile-char interactions on char gasification are not negligible. In this study, the effects of volatiles were examined with a novel fluidised-bed/fixed-bed reactor, and the mechanisms and kinetics model of the char gasification and volatile-char interactions were discussed to describe quantitatively the inhibition of volatiles about char gasification. Victorian brown coal sample was gasified with steam at 800 °C at various feeding rates. As a result, char yields became higher at higher feeding rate at the same feeding time because of the volatile-char interactions. The elementary reactions of the char gasification and volatile-char interactions were proposed and the L-H type reaction rate equations for brown coal gasification were newly derived, and the kinetics model was verified by the comparison with experiments. The experimental data of the char yields and the concentrations of Na in gasified char were able to be estimated by theproposed kinetics model. This model would be useful to estimate the performance of the gasifier for Victorian brown coal.